Exploring the perceived impact of a leadership training module on clinical family medicine practice: a qualitative study - Dladla, Samantha (Division of Family Medicine, 2025)
Background: Family physicians are the senior clinicians responsible for clinical governance in the District Health System. Their training programmes must prepare them for the leadership roles they are expected to fulfil. At the University of Cape Town, family medicine registrars enrolled in a four-year Masters of Medicine (MMed) degree complete a four-month Leadership and Governance module during their third year of study. This module consists of seminars, a leadership profile, and critical reflection sessions. While the immediate feedback is useful, the relevance of this module to the actual work of these family physicians is not known. This study aimed to understand how the postgraduate L&G module at UCT helped prepare qualified family physicians working in the Western Cape Province public sector for their leadership role. Methods: Ten graduates were purposively sampled for online semi-structured interviews, which were recorded, transcribed, and analysed using the framework method. Data were analysed deductively and assigned to the relevant theme. Where coded data did not fit into these themes, a new theme was generated if the data was sufficiently cohesive. Results: The following themes were identified : key leadership qualities and fit for purpose training. Two additional themes were generated: early experiences of the FP as clinical leaders and Resources used by FPs. Conclusion: This qualitative study explored recently qualified family physician consultants perceptions on their leadership training. Four key themes emerged that describe their leadership journeys, highlighting aspects of the current training that could be strengthened. Future research should explore workplace-based leadership training models, the impact of leadership role-modelling, and provide ongoing evaluation of fit for purpose training programmes.